Microwave-assisted Passerini reactions under solvent-free conditions - Barreto, Angélica de Fátima S (2011)
Various α-acyloxy carboxyamides were easily obtained combining three building blocks in one step: a carboxylic acid, an aldehyde and an isonitrile (Passerini reaction), using microwave irradiation under solvent-free conditions. The products were obtained in good yields (61-90%) and in short reaction times (< 5 min), using two different temperatures (60 and 120 ºC). At 120 ºC, the yields were higher and the reactions faster (< 1 min). Most of the obtained products are multifunctional allowing their application in consecutive Passerini reactions